Bone Mineral Density and Body Mass Index in Postmenopausal Women - Nahar, Kamrun; Al Zahid Bhuiyan, Mohammed Mehedi; Mia, Md Azzad; Hossain, Arshad; Tasnim, Humayra (Bangladesh Medical Journal, 2021)
Osteoporosis is a typical medical issue that overwhelmingly influences postmenopausal women. A bone density test is the only test that can diagnose osteoporosis before a broken bone occurs. The aims of this study was to find out the relationship between bone mineral density (BMD) and body mass index (BMI) in postmenopausal females. This cross sectional descriptive study was carried out in the Institute of Nuclear Medicine and Allied Sciences (INMAS), Sylhet. Study subjects comprised of 117 postmenopausal women between ages 45 to 85 years, with a mean age of 60.8 ± 9.2 years, who underwent BMD scan from January 2018 to June 2019. Duration of the study was 5 months ( march 2019 to august 2019). BMD was measured by the MedilinkMedix DR system. Findings of BMD of right femur showed osteopenia and osteoporosis (low BMD) in most of the women with under weight (81.0%) about one third (32.3%) of normal body weight and few (16.7%) of them over weight. Contrarily in left femur, low BMD was found in 08 (80.0%), 25 (40.3%) and 6 (16.7%) among underweight, normal, overweight patients respectively. According to BMI compare to the lumbar spine, low BMD was found in 48 (77.4%), 10 (100 %), 20 (55.6%), 03 (33.3%) among normal, underweight, overweight, and obese patients respectively. Relationship among BMD and BMI was found statistically significant in the both femurs (p < 0.001) and lumbar spine (p = 0.02). Low BMD was more severe in the 65-74 years’ age group in both femurs 65.4% and 65-85 years’ age group in lumbar spine 84.6% compare to other groups. The findings of this study reveal that low BMI and aging are associated with bone loss. Routine BMD checking in postmenopausal women might be important to initiate an early clinical intervention for osteoporosis. Bangladesh Med J. 2020 Sept; 49(3) : 22-28